(3cJGH SjHhjgs - (3YeQh Hf YKeGf Hf bfHQ GdMGQKj, SjHhjg, CHh HTQ , J (B180 (3g` s; (3SjHhjg , YeQh Hf YKeGf Hf bfHQ GdMGQKj, SjHhjg,J (B180 (3g` s
(3ChdgG (B:s
(3bGd CHh YHO Gddg eMeO Hf jMji bQCJ Ydi GHf hdGO hgh jfXQ ai cJGHg CHjg Yf SjHhjg (B: (3GdMeO ddg GdPi GaJJM HGdMeO cJGHg hLYdg BNQ OYGA Cgd MfJg s
(3BNQgG (B:s
(3heKd gPG bhd HYVge YdeGA Hfh adGf eMPha GddGe hgh jQjO (B: (3Ydi GdeGA Hfh adGf hgj YQHjI GfJgi cJGH SjHhjg hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3QhGjI CHh YHO Gddg eMeO Hf jMji GdQjGU Yf GHf hdGO hGHf GdfMGS GdfSNI efbhdI Yf fSNI YdjgG NW GdReNTQi PcQ ai ChdgG WQbG cKjQI dQhGjI GdcJGH hQehR GdQhGIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B10s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs